General Practice Outside Ministry of Health in Nepal - Aacharya, Ramesh P; Tiwari, Sanjeeb (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Postgraduate academic degree - Medical Doctorate in General Practice (MDGP) was started back in 1979 in order to support the health care system under the Ministry of Health (MoH). The curriculum of the post graduate program in General Practice in Nepal has been designed to develop comprehensive and effective health care as well as timely life-saving surgical services in the district hospital. Right from the beginning, compliance from the employer side has been less than expected. The ministry does not send the candidates for study. Furthermore, the graduates are not employed appropriately. The efforts of agencies like International Nepal Fellowship and Safe Motherhood Program in the past have failed. However, organizations like General Practitioners Association of Nepal (GPAN) and Nick Simon Institute (NSI) are pursuing hard to support the government system in order to provide comprehensive health care to the needy people. A holistic approach is necessary to review the policy related to MDGPs recruitment and retention. To improve retention of GPs in the rural areas, there is a need to have a clear career ladder, with recognition of the value of service in rural areas.